Who Put the Super in Superhero? Transformation and Heroism as a Function of Evolution - Ross, Susan L. (Frontiers in Psychology, 2019)
Transformation and heroism are reciprocally related. Transformation produces an individual that others may call hero; one who inspires, guides, and protects something precious—an ordinary extraordinary person, master of the self. Heroes exhibit the further reaches of human development by transforming into entirely new, resplendent individuals that demonstrate valuable capacities whiles still being mortal. Because transformation is the means through which heroes are made, a more thorough understanding of the forces affecting transformation may advance collective understanding of the demands upon the individual. Founded on the scholarship of seminal authors of depth psychology, East Indian spirituality, anthropology, physics, mythology, Hermetic science, and other disciplines, this paper argues that a hero develops through both natural and supernatural processes, which can eventually produce a transhuman or superhero—depending on one's perspective, one who is natural (bound by nature) and supernatural (beyond nature). If this psychospiritual proposition has merit, advancement from ordinary to hero and from hero to super hero—each resulting from trans-form-ation—constitutes a subtle yet fundamental change in form, a microevolution of a subsect of individuals. The progressive framework begins with a description of patterns of evolution salient to heroism and transformation; an exploration of four key “laws” that govern the realm of matter, which support and delimit the budding hero as an earth-bound human; and an examination of four “supernatural” abilities the initiate must cultivate and enact in order to transform. The heart of the paper is a detailed guide identifying when during the process of transformation, the initiate can expect to receive the support of natural processes, when to be vigilant for beyond nature or Divine intervention, and when to intervene with “supernatural” activities. The framework culminates with an elucidation of how the ordinary yet heroic individual becomes a superhero or transhuman as outlined by spiritual teacher Sri Aurobindo, through three transformations of biopsychosocial maturation and spiritual realization.